2014
DOI: 10.1172/jci76864
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial VEGF induces placental sFLT1 and leads to pregnancy complications

Abstract: Figure 8. Effects of placental sFlt1 knockdown with or without endometrial VEGF overexpression. (A-L) Placental sFlt1 knockdown. Upon placentaspecific sFLT1 shRNA expression, widespread hemorrhaging in the fetus (B) and at the placental-decidual junction (D) was observed on GD18 compared with controls (A and C). Histological examination of sFLT1 shRNA-expressing placentas revealed extraordinary dilation of some maternal blood sinuses (arrowheads) in the labyrinth (E and F) and fibrin deposition (arrow) in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
166
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(183 citation statements)
references
References 52 publications
11
166
1
2
Order By: Relevance
“…The therapeutic dose range of ELP‐VEGF (1–5 mg/kg per day) is equivalent to a free VEGF dose of 187 to 932 μg/kg per day because of the differences in molecular weight between the free and ELP‐fused cytokine. The efficacy observed at these doses is consistent with previous studies using the free cytokine, which showed normalization of blood pressure at doses in the range of 180 to 400 μg/kg per day 36, 64. The ameliorative effect of ELP‐VEGF on mean arterial pressure may be the result of 2 possible mechanisms.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The therapeutic dose range of ELP‐VEGF (1–5 mg/kg per day) is equivalent to a free VEGF dose of 187 to 932 μg/kg per day because of the differences in molecular weight between the free and ELP‐fused cytokine. The efficacy observed at these doses is consistent with previous studies using the free cytokine, which showed normalization of blood pressure at doses in the range of 180 to 400 μg/kg per day 36, 64. The ameliorative effect of ELP‐VEGF on mean arterial pressure may be the result of 2 possible mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…Studies using viral overexpression33, 57, 59, 60, 61 or direct infusion of sFlt‐132, 55, 62, 63 have demonstrated a critical role for this anti‐angiogenic factor for induction of hypertension and renal damage during pregnancy. Previous studies using exogenous VEGF infusion have reported reduced circulating sFlt‐1 levels 36, 64. However, induction of local VEGF expression in the maternal decidua was shown to actually promote increased placental sFlt‐1 expression in the cytotrophoblasts,65 suggesting a protective role for placental sFlt‐1 against maternal overproduction of VEGF 66.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In this regard, overexpression of sFlt-1 by decidual cells produces a PE-like syndrome in mice (53). Finally, a decidualization defect could help explain our previous finding that isolation and culture of CTBs from sPE placentas reversed the gene dysregulation that was initially observed (9).…”
Section: Discussionmentioning
confidence: 80%